Collaborative operation and application influence of sprinkler drip irrigation: A systematic progress review - Liang, Zhongwei; Zou, Tao; Liu, Xiaochu; Liu, Guiyun; Liu, Zheng (International Journal of Agricultural and Biological Engineering, 2023)
Considering the high-quality requirements related to agricultural crop production, the collaborative operation and application influence of sprinkler drip irrigation is an important issue in precision agriculture. The objective of this review is to give a comprehensive demonstration focusing on the subject of collaborative operation and application influence of sprinkler drip irrigation, by using a set of comparative analysis and literature bibliometric maps, therefore the sprinkler drip irrigation quality considering actual influential factors could be determined and analyzed. This review establishes on a broad spectrum of agricultural drip irrigation performance, throughout its whole procedure of collaborative monitoring, irrigation scheduling, application efficiency, and environmental influence, covering such aspects as soil physicochemical quality, irrigation scheduling, water resource redistribution, crop productivity, tillage management, climate adaptation, and environmental monitoring, etc. This review indicates that, the irrigation efficiency and drip infiltration quality of soil field can be planned precisely and allocated reasonably by sprinkler drip irrigation, which has extraordinary infiltration capability and enables much better performance, than that of other ordinary irrigation approaches in accuracy, stability, regularity, and efficiency. Thereafter, the investigation on the collaborative operation and application influence of sprinkler drip irrigation can be used to ensure the infiltration uniformity of moisture distribution, and then the high-quality requirements of practical irrigation performance can be met, too. This systematic review facilitates the productive soil-moisture-environment management for precision irrigation and agricultural production.Keywords: sprinkler drip irrigation, collaborative operation, irrigation scheduling, application efficiency, environmental influence, reviewDOI: 10.25165/j.ijabe.20231605.7198Citation: Liang Z W, Zou T, Liu X C, Liu G Y, Liu Z. The collaborative operation and application influence of sprinkler drip irrigation: a systematic progress review. Int J Agric & Biol Eng, 2023; 16(5): 12–27.